A comparative study for accessing primary healthcare between planning assessment and actual utilization for older adults: a case from Dalian City, China - Bai, Jiayuan; Lu, Wei (Frontiers in Public Health, 2023)
As China has rapidly evolved into a dominant stage of the aging society, China government has developed a community-oriented primary health care system to vigorously expedite the transfer of PHC from higher-level hospitals to community health centers (CHCs). However, current planning standards for CHCs have not considered the heterogeneity of the elderly in supply-demand services, such that the areas with severe aging may exhibit misestimated accessibility. This study placed a focus on the gap in accessing the CHC services between planning assessment and actual utilization for the elderly. The accessibility of CHCs for communities with different aging levels was measured in the city area of Dalian using the check-in and survey data from CHCs during the COVID-19 pandemic. A comparison model was built to calculate matching probability using a modified Gaussian Two-step Floating Catchment Area (G2SFCA) method. As indicated by the results, the average matching probability of the elderly reached 76%, and the spatial distribution of mismatch accessibility was correlated with across-catchment visits and the uneven supply-demand ratio. Nearly 10% of communities in the Primary Health Care Shortage Area (PHCSA) were ignored through the current planning assessment. The above-mentioned findings can contribute to the increase of measurement accuracy while indicating the aging-adaptive planning for PHC.